An Analysis of Cohesion and Coherence in Written Text of Line Today about Wedding Kahiyang Ayu and Bobby Nasution - Tarina Dashela; Yeni Mustika (STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
This research is about an analysis of cohesion and coherence in written text of line today about wedding Kahiyang Ayu and Bobby Nasution. It is aimed to analyze the term of cohesion and coherence in the following text. The descriptive analysis is used as the methodology. The data source is from Line Today. Through the text the researchers found the lexical cohesion, grammatical cohesion, and rhetorical cohesion in cohesion analysis. The text also involving the Micro-Level Coherence and Macro-Level Coherence. In conclusion, the result of analysis showed that the text is cohesive but not coherent enough. Keyword: Analysis, Coherence, Cohesion, Written Text